Managing Students in Sexuality Education: “Love, Sex, and Dating” Based on the Qur'an in Educational Institutions - Anggraini, Helda Yusfarina; Intitsal, Amiratul Fadilah; Zamroni (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This research aims to describe the management of learners in Qur'an-based “love, sex, and dating” sexuality education in educational institutions. This research uses a qualitative approach with descriptive type. Researchers collected data using non-participant observation techniques, semi-structured interviews and documentation. At the analysis stage using the flow model technique with the stages of data condensation, data presentation, and finally drawing conclusions. The outcomes in this research are the management of students in sexuality education “love, sex, and dating” based on the Qur'an at SMP IT Madina carried out through several stages, namely the planning stage, the organising stage, the implementation stage and the supervision stage. The conclusion of this research is that the management of students who have been implemented at SMP IT Madina has finally given birth to several activity programs in the implementation of al-qur'an-based “love, sex, and dating” sexuality education, including starting from the new student admission program, learning process program, counselling guidance program, and tausiyah program. Some of the activities that have been carried out are slowly able to equip students in protecting dignity and controlling themselves wisely and responsibly in their sexual lives.